0311 The day after: how does a poor sleep perception affect pain during the night?. (25th May 2022) - Morelhao, Priscila; Fernandes, Guilherme; Dokkedal-Silva, Vinícius; Pires, Gabriel; Tufik, Sergio; Andersen, Monica
Abstract: Introduction: Senescence generates repercussions on sleep, including increased difficulty to initiate and maintain sleep, more awakenings, diurnal naps, and a propensity to polyphasic sleep. These disorders might be more common in older individuals with musculoskeletal pain. In this sense, the relationship between sleep and pain is considered to be bidirectional. However, it is unclear in the literature whether feeling pain during the night could be associated with poor subjective sleep quality. Our objective was to describe a measurement model that appropriately conveys the link between sleep and feeling pain at night. Methods: A cross-sectional analysis was conducted, using a dataset from the 2015 São Paulo Epidemiological Sleep Study (EPISONO), including only individuals aged 60 years or more. Two constructs were formulated: an objective sleep quality construct, based on the polysomnography (PSG) performed on all EPISONO volunteers and a subjective sleep quality construct, formed by the self-reported answers in the Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI). Musculoskeletal pain was assessed by 1. Did you feel any pain during the night? 2. Did you wake up feeling pain? (Possible answers: "Yes" or "No"). We used exploratory factor analysis and structural equation modelling to identify the significant variables. Results: A total of 152 older adults was analyzed in this study. The PSQI and ISI indicate poor perception of sleep or a high frequency of sleep complaints in proportion to their score, the resulting latent factor was labelled poor sleep perception. The exploratory factor analysis assessed the measurement models of the latent factors and resulted in the inclusion of sleep-related variables: wake after sleep onset, sleep efficiency, total sleep time, latency to sleep onset and amount of N1 stage in the objective sleep quality factor. However, this factor was not associated with felling pain during the night and woke up with pain. Conclusion: Our findings suggest that poor sleep perception was associated with feeling pain at night in older adults. These results contribute for the improvement of future clinical evaluations of patients presenting musculoskeletal pain and sleep complaints and highlight the importance of considering both factors simultaneously during treatment. Support (If Any): The study was supported by Associação Fundo de Incentivo à Pesquisa (AFIP) and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES Finance Code 001 to GLF) and Conselho Nacional de Desenvolvimento Científico Tecnológico (CNPq–Grant #133397/2017-3, #141445/2021-1 to GLF); MLA and ST are Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) fellowship recipients.